Clinical and genetic investigation of 17 Japanese patients with hyperekplexia. (30th October 2014) - Mine, Jun; Taketani, Takeshi; Yoshida, Kazushi; Yokochi, Fusako; Kobayashi, Junpei; Maruyama, Koichi; Nanishi, Etsuro; Ono, Mayumi; Yokoyama, Atsushi; Arai, Hidee; Tamaura, Shiho; Suzuki, Yasuhiro; et al.
<x xml:space="preserve">Abstract</x> Aim The aim of the study was to determine clinical and genetic characteristics of Japanese patients with hyperekplexia. Method Clinical courses, responses to antiepileptic drugs, outcomes, and genetic testing were investigated in 17 Japanese patients (nine males, eight females, median age 1y, range birth–45y) with hyperekplexia. Results In all patients, muscle stiffness and startle responses appeared soon after birth. Only seven patients were diagnosed with hyperekplexia before 1 year of age. Seven patients had been misdiagnosed with other disorders such as epilepsy and adult‐onset anxiety neurosis. Umbilical/inguinal hernias were seen in 10 patients. Life‐threatening events were noted in four patients. Clonazepam was the most effective drug. Muscle stiffness completely disappeared in 12 patients before 5 years of age, whereas startle responses resolved in only three patients. Mutations in the GLRA1 and GLRB genes were identified in 16 patients and one patient respectively. In 14 patients, the mutation showed autosomal dominant inheritance; in the other three, inheritance was autosomal recessive. p.R271Q of GLRA1 was the most frequent mutation, found in 10 patients. Novel mutations, p.A272P and p.A384P of GLRA1, were detected. Clinical severity and outcome varied even in the same family. Interpretation Early correct diagnosis is essential for prevention of accidental injuries and to provide appropriate treatments for hyperekplexia. Clonazepam is effective, although the time taken for startle responses to resolve varied.